IAEA Contribution to Nanosized Targeted Radiopharmaceuticals for Drug Delivery - Amir R. Jalilian; Blanca Ocampo-García; Wanvimol Pasanphan; Tamer M. Sakr; Laura Melendez-Alafort; Mariano Grasselli; Ademar B. Lugao; Hassan Yousefnia; Clelia Dispenza; Siti Mohd Janib; Irfan U. Khan; Michał Maurin; et al. (MDPI AG, 2022)
The rapidly growing interest in the application of nanoscience in the future design of radiopharmaceuticals and the development of nanosized radiopharmaceuticals in the late 2000's, resulted in the creation of a Coordinated Research Project (CRP) by the International Atomic Energy Agency (IAEA) in 2014. This CRP entitled 'Nanosized delivery systems for radiopharmaceuticals' involved a team of expert scientist from various member states. This team of scientists worked on a number of cutting-edge areas of nanoscience with a focus on developing well-defined, highly effective and site-specific delivery systems of radiopharmaceuticals. Specifically, focus areas of various teams of scientists comprised of the development of nanoparticles (NPs) based on metals, polymers, and gels, and their conjugation/encapsulation or decoration with various tumor avid ligands such as peptides, folates, and small molecule phytochemicals. The research and development efforts also comprised of developing optimum radiolabeling methods of various nano vectors using diagnostic and therapeutic radionuclides including Tc-99m, Ga-68, Lu-177 and Au-198. Concerted efforts of teams of scientists within this CRP has resulted in the development of various protocols and guidelines on delivery systems of nanoradiopharmaceuticals, training of numerous graduate students/post-doctoral fellows and publications in peer reviewed journals while establishing numerous productive scientific networks in various participating member states. Some of the innovative nanoconstructs were chosen for further preclinical applications-all aimed at ultimate clinical translation for treating human cancer patients. This review article summarizes outcomes of this major international scientific endeavor.